Evolution of medical students’ tolerance for uncertainty throughout their curriculum: a systematic mixed studies review protocol - Alain Lescoat; Thierry Pelaccia; Nicolas Belhomme; François Robin; Pierre Pottier; Emmanuel Triby (BMJ Open)
Introduction Understanding how uncertainty tolerance (UT) evolves in medical students is crucial to identify training needs and implement effective interventions. However, the dynamic nature of UT and the mechanisms behind its changes over time remain poorly understood. This systematic review aims to map the development of UT in medical students across the course of their training by synthesising the available evidence. We will adopt a systematic mixed studies review approach to provide an integrative synthesis of both quantitative and qualitative data, offering a comprehensive overview of UT temporal evolution.Method and analysis The protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We will conduct searches in Embase, Medline, Cumulative Index to Nursing and Allied Health Literature, ERIC, Cochrane Library and PsycINFO, from inception to July 2026. We will manually search the references of included studies and track citations through Google Scholar to identify additional eligible studies. Two reviewers will independently extract data from each eligible study using a pre-piloted Microsoft Excel data extraction form. A thematic synthesis will be employed to develop analytic themes from the existing literature, generating new concepts and explanatory hypotheses. Study quality will be evaluated using the QuADS score.Ethics and dissemination Ethical approval is not necessary for this systematic review, as no primary data will be collected. The protocol for this review has been registered with the International Prospective Register of Systematic Reviews PROSPERO: CRD42024591340.